Autonomous Tetramerization Domains in the Glycan-binding Receptors DC-SIGN and DC-SIGNR - Yu, Quan D. (Elsevier Ltd., 2009)
Multivalent binding of glycans on pathogens and on mammalian cells by the receptors DC-SIGN (CD209) and DC-SIGNR (L-SIGN, CD299) is dependent on correct disposition of the C-type carbohydrate-recognition domains projected at the C-terminal ends of necks at the cell surface. In the work reported here, neck domains of DC-SIGN and DC-SIGNR expressed in isolation are shown to form tetramers in the absence of the CRDs. Stability analysis indicates that interactions between the neck domains account fully for the stability of the tetrameric extracellular portions of the receptors. The neck domains are approximately 40% α-helical based on circular dichroism analysis. However, in contrast to other glycan-binding receptors in which fully helical neck regions are intimately associated with C-terminal C-type CRDs, the neck domains in DC-SIGN and DC-SIGNR act as autonomous tetramerization domains and the neck domains and CRDs are organized independently. Neck domains from polymorphic forms of DC-SIGNR that lack some of the repeat sequences show modestly reduced stability, but differences near the C-terminal end of the neck domains lead to significantly enhanced stability of DC-SIGNR tetramers compared to DC-SIGN.